Increasing surgical healthcare utilization for infants with congenital anomalies in Texas - Bea B. Jeon; Bea B. Jeon; Sarah Peiffer; Sarah Peiffer; Shannon M. Larabee; Shannon M. Larabee; Kathleen Hosek; Dailen Alonso; Timothy C. Lee; Timothy C. Lee; Sundeep G. Keswani; Sundeep G. Keswani; et al. (Frontiers in Surgery, 2025)
IntroductionCongenital anomalies (CAs) impact 3% of live births and account for disproportionately high healthcare costs. While many CAs require multidisciplinary care and surgical intervention, the overall financial impact of infants diagnosed with CA with surgical needs is unknown. We aim to evaluate and characterize the charges of care in infants with CA and surgical needs in Texas.MethodsA database study using the Texas Inpatient Public Use Data File was performed to query infants (<365 days) statewide from 1/2021 to 12/2021 for admissions with CA and involved organ system by ICD-10 codes. Encounters transferred to an outside hospital were excluded to avoid systematic double-counting. Descriptive statistics were performed.ResultsOf 376,215 total admissions, 81,666 had surgical needs with OR charges. While non-CA represent the majority of surgical admissions (63,895/81,666; 78.24%), CA-surgical admissions represent 73.3% ($4.766/$6.496 billion) surgical admissions charges. Of CA-surgical admissions, 78.9% were single organ-system (1CA) with 14.5% with two organ-systems (2CA), 4.0% with three organ-system (3CA) and 2.6% with 4 + organ-systems (4 + CA). The proportion of admissions with surgical needs increases with the number of CA organ-systems involved. The median charge per CA-surgical admission was $1,296 for1CA, $4,517 for 2CA, $20,272 for 3 CA, and $25,313 for 4 + CA compared to the $797 for non-CA surgical admissions. Surgical admission charges increase with the number of CA organ-systems involved.ConclusionsSurgical care of CA in infants is associated with significant healthcare utilization, accounting for $4.8 billion (73.4%) of all inpatient charges in 2021 despite representing a minority of admissions. Increasing number of CA organ-systems involved is associated with an increased proportion of patients with surgical admissions and increased median charge of admission.